2(3-2z)-3(2z+7)=z-21

Simple and best practice solution for 2(3-2z)-3(2z+7)=z-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3-2z)-3(2z+7)=z-21 equation:


Simplifying
2(3 + -2z) + -3(2z + 7) = z + -21
(3 * 2 + -2z * 2) + -3(2z + 7) = z + -21
(6 + -4z) + -3(2z + 7) = z + -21

Reorder the terms:
6 + -4z + -3(7 + 2z) = z + -21
6 + -4z + (7 * -3 + 2z * -3) = z + -21
6 + -4z + (-21 + -6z) = z + -21

Reorder the terms:
6 + -21 + -4z + -6z = z + -21

Combine like terms: 6 + -21 = -15
-15 + -4z + -6z = z + -21

Combine like terms: -4z + -6z = -10z
-15 + -10z = z + -21

Reorder the terms:
-15 + -10z = -21 + z

Solving
-15 + -10z = -21 + z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
-15 + -10z + -1z = -21 + z + -1z

Combine like terms: -10z + -1z = -11z
-15 + -11z = -21 + z + -1z

Combine like terms: z + -1z = 0
-15 + -11z = -21 + 0
-15 + -11z = -21

Add '15' to each side of the equation.
-15 + 15 + -11z = -21 + 15

Combine like terms: -15 + 15 = 0
0 + -11z = -21 + 15
-11z = -21 + 15

Combine like terms: -21 + 15 = -6
-11z = -6

Divide each side by '-11'.
z = 0.5454545455

Simplifying
z = 0.5454545455

See similar equations:

| 8(x+8)+6=10x-2(x-5) | | 5(x+2)=3X-(x-4) | | -3(2m-4)=21 | | 6x/7x-49 | | -1/4(12x-16)= | | b^2-14b=-48 | | b^2-14b=48 | | -384=-16m | | 6x-6=6x+54 | | 2=3+x^2 | | -6-2t=-1t-1 | | -4/7÷3/14 | | 450=25(h) | | 36/m=3 | | 8=9+x^2 | | 2(-2)+y=-3 | | 4-5x-7x+16= | | 4y+23=36 | | Log[4](2x-6)=3 | | (3x+60)=360 | | X-5/4-1=x-4/3 | | 3z/8=16 | | y/-8=0 | | 3(3x+4)+6(x-1)= | | 2ax+2b=2c | | b/-7=-40 | | 40-5x=70 | | 0=x^3+0.5x^2+8+x | | 2z=7 | | cos(x)+cos^2(x)-sin^2(x)=0 | | x+3x+6x-4=180 | | 10=4(a-2) |

Equations solver categories